Production efficiency of Inpago Unsoed-1 and Situbagendit rice farming in Central Java, Indonesia - ALTRI MULYANI; Dwidjono Hadi Darwanto; Sri Widodo; Masyhuri Masyhuri (Society for Indonesian Biodiversity, 2020)
Abstract. Mulyani A, Darwanto D, Widodo S, Masyuri. 2020. Production efficiency of Inpago Unsoed-1 and Situbagendit rice farming in Central Java, Indonesia. Biodiversitas 12: 3276-3286.  Inpago Unsoed-1 rice is a new superior rice variety that is not as familiar as Situbagendit variety for farmers in Indonesia. As one of the new superior rice variety, Inpago Unsoed-1 is expected to improve farm business efficiency so that it can increase farmers' income. This study was conducted to figure out the factors influencing the production of Inpago Unsoed-1 and Situbagendit rice in Province of Central Java, and to recognize the level of technical, allocative and economic efficiencies of Inpago Unsoed-1 and Situbagendit rice farming in Province of Central Java. Research sites included selected regencies in Province of Central Jawa, such as Banyumas, Purbalingga, and Cilacap. Meanwhile, the selected districts were Kalibagor (Banyumas); Kalimanah, Kemangkon, Bukateja, Kutasari, Kaligondang, and Bobotsari (Purbalingga); and Gandrungmangu (Cilacap). Data were collected by direct observation and interviews using semi-structured questionnaire. The sampling technique used non-probability sampling using a purposive sampling method. Data were collected during December 2018-May 2019, 147 farmers were sampled, consisting of 71 and 76 farmers for Inpago Unsoed-1 and Situbagendit, respectively. Data were analyzed by using Cobb-Douglas production function and function of Stochastic Frontier. The results showed that production factors of land acreage (ha) and P fertilizer (kg) positively affected the production of Inpago Unsoed-1 rice, whereas seeds (kg), N fertilizer (kg) and pesticide (l) had negative impact on its production. On Situbagendit rice production, the positive and negative effects were revealed by land acreage (ha) as well as pesticide (l) and N fertilizer (kg), respectively. Technical, economic, and allocative efficiencies on Inpago Unsoed-1 rice farming were 0.75, 0.65, and 0.88, respectively, which were higher than those of Situbagendit, i.e. 0.73, 0.54 and 0.75, respectively.